Design and synthesis of 11 alpha-substituted bile acid derivatives as potential anti-tuberculosis agents - Pore, Vandana S.; Divse, Jaisingh M.; Charolkar, Chaitanya R.; Nawale, Laxman U.; Khedkar, Vijay M.; Sarkar, Dhiman (Bioorganic & Medicinal Chemistry Letters, 2015)
We have synthesized a series of novel 11 alpha-triazoyl bile acid derivatives. In addition, we also have synthesized N-alkyl and N-acyl derivatives of C-11 amino bile acid esters. All the compounds were evaluated for the inhibitory activity against Mycobacterium tuberculosis H37Ra (MTB) at 30 mu g/mL level. Four lead compounds (2b, 3, 7 and 8) were further confirmed from their dose dependent effect against MTB. These compounds were found to be active against Dormant and active stage MTB under both in vitro as well as within THP1 host macrophages. The most promising compound 2b showed strong antitubercular activities against MTB under in vitro and ex vivo (IC90 value of similar to 3 mu g/mL) conditions and almost insignificant cytotoxicity up to 100 mu g/mL against THP-1, A549 and PANC-1 human cancer cell lines. Inactivity of all these compounds against Gram positive and Gram negative bacteria indicates their specificity. Molecular docking studies of these compounds into the active site of DprE1 enzyme revealed a similar binding mode to native ligands in the crystal structure thereby helping to establish a structural basis of inhibition of MTB. The synthesized compounds were analyzed for ADME properties and showed potential to develop good oral drug candidates. Our results clearly indicate the identification of some novel, selective and specific inhibitors against MTB that can be explored further for potential antitubercular drug. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Antituberculosis; Bile acids; Cycloaddition; Docking study; In silico ADME

Design and synthesis of 2-amino-thiophene-proline-conjugates and their anti-tubercular activity against mycobacterium tuberculosis H37Ra - Baravkar, Sachin B.; Wagh, Mahendra A.; Nawale, Laxman U.; Choudhari, Amit S.; Bhansali, Sujit; Sarkar, Dhiman; Sanjayan, Gangadhar J. (ChemistrySelect, 2019)
The emergence of extensively drug resistant tuberculosis (XDRTB) and multi-drug resistant tuberculosis (MDR-TB) has necessitated the development of new drugs with short chemotherapy treatment regime and cost effectiveness. To overcome these challenges, we are reporting the synthesis of a series of 2-amino-thiophene-proline-conjugates which show potent invino and ex-vivo anti-tubercular (anti-TB) activity against mycobacterium tuberculosis (rntb) H37Ra. The synthesis of these 2-amino-thiophene-proline-conjugates was carried out via solution phase peptide coupling reactions using methyl-2aminothiophene-3-carboxylate 8 as an intermediate obtained by modified gewald reaction. Intermediate 8 was coupled with different amino acids to obtain dipeptides 3, 4, 5, 6a and 7. Priliminary anti-TB assay data encoureaged us to synthesize modified proline derivatives 6b-6k via formation of a benzoxazinone intermediate 16. Most of these conjugates are active against mtb H37Ra in both active (A) and dormant (D) strains. They are also active against drug resistant mtb H37Ra strains. A trifluoroethyl ester analog, 6i was the most potent among the series [MIC 1 mu g/mL] along with 6f and 6g [MIC 2-6 mu g/mL]. Cytotoxicity studies suggested that, these compounds are less cytotoxic to human cell lines HeLa, MCF-7, HUVEC and hence possess high selectivity index (SI). Docking studies revealed that the binding mode of most active compounds 6i, 6g and 6f is in accordance with their bioactivity studies having docking score 8.969, 8.446 and 7.865, respectively. More- over, in sllico ADME properties suggest that all the compounds possess drug like properties.
Keywords: 2-aminothiophene; Anti-tubercular; docking studies; Inh A gene; selectivity index